Ferrography-based Failure Analysis to Engine on Railway Large Maintenance Machinery - LIU Tiejun; HE Xueke (机车电传动)
With sampling lubricants of large maintenance machinery engine and analyzing its ferrography image, a method of diagnosis on the engine failure was put forward. Practice verified that the ferrography-based analysis technology was a very effective means to study mechanism wear and monitor wear condition of the machine.